FAKTOR-FAKTOR YANG MEMPENGARUHI PROFESIONALISME GURU MTs NEGERI DI BALIKPAPAN TIMUR - Tutik Yuliani (EQUILIBRIUM : Jurnal Ilmiah Ekonomi dan Pembelajarannya, 2016)
This study aims to determine whether there is (1) Effect on Teacher’s Competence towards Their Professionalism (2) Influence of School Organizational Climate on Teacher’s Professionalism, and (3) Attitude towards Teacher’s Professionalism. Sample in this research is all teachers in State MTS in East Balikpapan. Technique for collecting the data were using questionnaires and documentation. Results of this study are teacher’s competence, organizational climate and attitudes simultaneously influence professionalism of teachers in State MTS in East Balikpapan. We can conclude that School Organizational Climate has a dominant influence on the professionalism of teachers in East Balikpapan.